(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the development of library activities, the scientific and educational environment, and book culture during the Samanid period in the 9th–10th centuries in the regions of Transoxiana and Khorasan. It highlights the role of Bukhara and Samarkand as centers of science, where libraries served as essential sources for scholars, poets, and thinkers, based on historical evidence. Furthermore, the processes of book reproduction, collection, and preservation, as well as the role of libraries in socio-cultural life during the Samanid era, are examined. The findings show that libraries of the Samanid period not only contributed to scientific and educational progress but also laid an important foundation for the Eastern Renaissance